Greenwood Ave project [videorecording (DVD)] - Baccus, Terry; Thomas, George; Pearson, Bishop Carlton (Freestyle Digital Media, 2025)
Exploring resilience a century after the 1921 massacre, the documentary follows Greenwood Ave's ongoing fight against segregation, racism, and hate while rebuilding its Black-owned businesses and homes.